Mechanical properties of palm oil waste blended cement-based concrete containing spent garnet as partial fine aggregate replacement - Parsuraman, Jeyasaraniya; Rokiah, Othman; Mohd Arif, Sulaiman; Khairunisa, Muthusamy; Putra Jaya, Ramadhansyah; Youventharan, Duraisamy (Springer, 2025)
The growing emphasis on sustainability in construction has sparked increased interest in eco-friendly materials, particularly the development of green concrete to address environmental concerns. Sand, a crucial component in various construction materials and industries, faces rising demand due to population growth and higher living standards; however, its extraction significantly disrupts river ecosystems. In Malaysia, spent garnet from ship sandblasting has emerged as a promising additive to enhance concrete performance, with studies showing positive effects on compressive strength. This study investigates the impact of incorporating spent garnet (SG) as a partial replacement for fine aggregates, aiming to determine the optimal replacement percentage that achieves 30 MPa compressive strength within 28 days. Concrete mixes were prepared using three water-cement (w/c) ratios (0.45, 0.50, 0.55) and a conventional cement-sand ratio, incorporating 10% Palm Oil Fuel Ash (POFA) as a cement substitute and SG at 0% to 40% by weight of fine aggregate. A total of 135 cubes and cylinders were cast and tested for slump, compressive strength, and splitting tensile strength according to ASTM standards. Sieve analysis showed that sand performed better than SG at finer particle sizes, while higher w/c ratios improved workability with increasing SG content. The optimum mechanical performance across all w/c ratios was recorded at 30% SG, beyond which strength declined. It is recommended that future studies explore long-term durability, microstructural behavior, and environmental impacts of POFA-SG concrete through additional tests such as water absorption, penetration resistance, and ultrasonic pulse velocity (UPV). These will help identify internal flaws, assess porosity, and confirm homogeneity. Moreover, microstructural evaluations like SEM and detailed chemical characterizations—currently beyond the scope of this study—will be addressed in a separate companion paper, offering a more holistic understanding of SG and POFA in sustainable concrete development.